Dynamics of The Rules for Changing Sharia Law According to Ibnul Qayyim Al-Jauziyyah - Rudin, Syafaat; Kurniati, Kurniati; Musyahid, Achmad; Rahmat, Fajar; As'ad, Muslahuddin (Journal of Family Law and Islamic Court, 2024)
The diversity of human life necessitates order to achieve social harmony. This study examines the significance of divine law (syari’ah ilahiyyah) as superior to tasyri’ wad’i (man-made law), focusing on the consistency of Islamic law and its relationship to the fiqh maxim “Laa Yunkaru Taghayyur al-Ahkam bi Taghayyur al-Azman” (legal rulings may change with changing times). Using a literature-based method, the analysis incorporates classical and contemporary scholarly perspectives alongside practical applications of the maxim. The findings reveal that rulings derived directly from textual evidence (nass) are immutable, whereas those based on custom (urf), public interest (maslahah), or independent reasoning (ijtihad) may adapt to changing contexts. The maxim is narrowly applied to rulings influenced by customs, leaving core scriptural rulings unchanged. Examples include theft punishments adjusted for customary definitions of safekeeping, evolving zakat policies, and contemporary regulations such as traffic laws. These findings affirm that Islamic law combines permanence in foundational principles with flexibility in contextual applications, ensuring its relevance across times and places. The study concludes that understanding the boundaries of this fiqh maxim is crucial for maintaining the balance between the timelessness of Islamic law and its adaptability to modern challenges, preserving both its authenticity and practical utility.--Keberagaman kehidupan manusia memerlukan keteraturan untuk mencapai harmoni sosial. Studi ini mengkaji pentingnya hukum ilahi (syari’ah ilahiyyah) yang dianggap lebih unggul dibandingkan dengan tasyri’ wad’i (hukum buatan manusia), dengan fokus pada konsistensi hukum Islam dan hubungannya dengan kaidah fiqih “Laa Yunkaru Taghayyur al-Ahkam bi Taghayyur al-Azman” (hukum dapat berubah sesuai dengan perubahan zaman). Dengan pendekatan berbasis literatur, analisis ini mencakup perspektif ulama klasik dan kontemporer serta aplikasi praktis dari kaidah tersebut. Temuan menunjukkan bahwa hukum yang bersumber langsung dari nash bersifat tetap, sementara hukum yang didasarkan pada adat (urf), kemaslahatan (maslahah), atau ijtihad dapat disesuaikan dengan konteks yang berubah. Kaidah ini diterapkan secara terbatas pada hukum yang dipengaruhi oleh adat kebiasaan, sementara hukum nash tetap tidak berubah. Contoh penerapan mencakup hukuman pencurian yang disesuaikan dengan definisi adat penyimpanan barang, kebijakan zakat yang berkembang, dan peraturan kontemporer seperti lalu lintas. Temuan ini menegaskan bahwa hukum Islam menggabungkan keabadian prinsip-prinsip dasar dengan fleksibilitas dalam aplikasi kontekstual, sehingga memastikan relevansinya di berbagai waktu dan tempat. Studi ini menyimpulkan bahwa pemahaman batasan penerapan kaidah fiqih ini sangat penting untuk menjaga keseimbangan antara keabadian hukum Islam dan kemampuannya beradaptasi dengan tantangan modern, sekaligus mempertahankan keaslian dan kegunaannya secara praktis.